Roses and rot - Howard, Kat (Saga Press, 2016)
Imogen has grown up reading fairy tales about mothers who die and make way for cruel stepmothers. As a child, she used to lie in bed wishing that her life would become one of these tragic fairy tales because she couldn't imagine how a stepmother could be worse than her mother now. As adults, Imogen and her sister Marin are accepted to an elite post-grad arts program; Imogen as a writer and Marin as a dancer. Soon enough, though, they realize that there's more to the school than meets the eye. Imogen might be living in the fairy tale she's dreamed about as a child, but it's one that will pit her against Marin if she decides to escape her past to find her heart's desire.